A participação da família no contexto escolar: um estudo realizado na EMEF “Netélcio Ferreira de Brito”, do projeto de assentamento PA Rio Gelado, em Novo Repartimento/PA - ALVES, Maria Antonia Moraes (2021)
This study is the result of a research entitled: "The Participation of the family in the school context: a study carried out in the EMEF ―Netélcio Ferreira de Brito‖, of the settlement Project P. A. Icy river, in new split/PA", whose main objective is to make a Reflection on the importance of family and school relationships, for a better school performance of children, especially students from 1st to 5th year, which is the focus of this study. Thus, a theoretical basis was first carried out based on the works of several renowned authors who made an approach to the topics developed in this study. Shortly thereafter, a field survey was carried out at the school "Netélcio Ferreira de Brito" whereby it was possible to do an investigation of its relationship with the families of its students who attend it. For the collection of the data, an interview consisted of 05 open questions on the issues rationed the subject of this study. The results were analyzed, taking into account the theoretical reasoning, being discussed and interpreted from the units of registration of the informants. In this way, the results revealed that the families of the school-field students have not been effectively involved in the educational process of their children/pupils and, consequently, the students ' school performance has worsened more and more.